Pengaruh Terapi Zikir Terhadap Penurunan Tanda Dan Gejala Halusinasi Pada Pasien Halusinasi - Herlambang; Emulyani Emulyani (HEALTH CARE : JURNAL KESEHATAN, 2020)
Hallucinations are one of the symptoms of mental disorder in which the patient experiences sensory changes in perception of the senses, the inability to distinguish internal stimuli (thoughts) and external stimuli (outside world) perceptions about the environment without objects. Dhikr or dhikrullah is etymologically defined as an activity to remember God. The purpose of this study was to determine the effect of zikir therapy on the reduction of hallucinatory signs and symptoms in hallucinatory patients at RSJ Tampan Riau Province. This type of research is quantitative with quasi-exprimental design, with a population of all hallucinatory patients in Sebayang and Indragiri room with a total of 21 patients, in which the sample in this study was the entire population of patients undergoing hallucinations who had undergone SP 1 (screaming) and SP 2 (talking with others), and tools for data collection using the format of soul nursing assessment by measuring the calculation of the frequency of occurrence of hallucinations before and after therapy given zikir, using data analysis bivariate analysis with T test, the results found that the value the average success of hallucinatory control in hallucinatory patients before the dhikr therapy was 16.90 and after zikir therapy was 5.48 with p value = 0.000 <0,05 it was found that the effect of zikir therapy on hallucinatory control in hallucinatory patients. The need for zikir therapy is carried out in the management of nursing services in standard service of operational procedures (SOP) on scheduled therapy.